2023
DOI: 10.1021/acsestengg.2c00317
|View full text |Cite
|
Sign up to set email alerts
|

Evaluation of the Relationship between Meteorological Variables and NOx Emission Factors Based on Plume-Chasing Measurements

Abstract: A relationship that links the accuracy of nitrogen oxide emission factors (NO x EFs) calculated from chasing measurements (EFchasing) to meteorological variables was developed. To quantitatively evaluate this relationship, we postulated an “effective ratio” concept based on the momentum wake theory. The effective ratio is considered a function of meteorological variables in the vehicle wake. A mobile platform was used to characterize NO x EFs by following tested vehicles that were installed with a portable e… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

1
0
0

Year Published

2024
2024
2024
2024

Publication Types

Select...
4
1

Relationship

1
4

Authors

Journals

citations
Cited by 5 publications
(1 citation statement)
references
References 40 publications
1
0
0
Order By: Relevance
“…We categorized these HDDV samples according to GVW and emission standards. Consistent with other real-world NOx emission measurement studies in China, 15,30 as shown in Figure 1, NOx emissions during the hot-running stage of China VI HDDVs from OBM (4.70 ± 0.09 g/kg-fuel, equivalent to 1.11 ± 0.03 g/kWh, see Supplementary Note 1 for unit conversion details) are substantially lower than those of China V vehicles (17.4 ± 1.34 g/kg-fuel, equivalent to 4.07 ± 0.33 g/kW h). NOx emissions of China V HDDVs increase with GVW, while those of China VI HDDVs stay consistent across different GVW groups.…”
Section: Real-world Nox Emissions Of Heavy-duty Fleetssupporting
confidence: 90%
“…We categorized these HDDV samples according to GVW and emission standards. Consistent with other real-world NOx emission measurement studies in China, 15,30 as shown in Figure 1, NOx emissions during the hot-running stage of China VI HDDVs from OBM (4.70 ± 0.09 g/kg-fuel, equivalent to 1.11 ± 0.03 g/kWh, see Supplementary Note 1 for unit conversion details) are substantially lower than those of China V vehicles (17.4 ± 1.34 g/kg-fuel, equivalent to 4.07 ± 0.33 g/kW h). NOx emissions of China V HDDVs increase with GVW, while those of China VI HDDVs stay consistent across different GVW groups.…”
Section: Real-world Nox Emissions Of Heavy-duty Fleetssupporting
confidence: 90%